Avaliação da flexibilidade do quadril em atletas de jiu-jitsu - Bizotto, Luana (My University, 2019)
Flexibility is important for athletes to improve movement quality, improve their technical skills, achieve greater range of motion, and prevent risks of joint injuries to stabilize the hip in their greater range of motion. The objective of this study is to evaluate the degree of hip flexibility in Jiu-Jitsu athletes. Quantitative, descriptive and exploratory research with transversal bias. The sample consisted of 46 men, between 18 and 45 years of age, attending a gymnasium in the city of Caxias do Sul, located in the State of Rio Grande do Sul. Flexiteste was used to verify the flexibility of the participants. For the statistical treatment, it was used the IBM ® SSPS Statistics 21.0 software and the Microsoft Excel program where descriptive measures (means, standard deviation, frequencies and percentages) were calculated and the ANOVA test was performed to compare paired sample means. Results: Through data analysis, it was found that only three of the assessments of flexibility in the athletes were statistically significant. Only in hip abduction, lateral flexion of left and right trunk were significant results, the rest did not have much alteration in the comparison of the results. Conclusion: With the data collected, we can conclude that Jiu-Jitsu fighters do not acquire complete hip joint flexibility with only sport training, so athletes need to seek specific training to reach good levels and improve performance during fights (sic).
A flexibilidade é importante para o atleta melhorar a qualidade de movimento, aperfeiçoar suas habilidades técnicas, atingir maiores amplitudes de movimento, prevenir riscos de lesões articulares para a estabilização do quadril na sua maior amplitude de movimento. O objetivo deste trabalho foi avaliar o grau de flexibilidade de quadril em atletas de Jiu-Jitsu. Pesquisa quantitativa, descritiva e exploratória com viés transversal. A amostra, por conveniência, contou com 46 homens, entre 18 a 45 anos, frequentadores de uma academia da cidade de Caxias do Sul, localizada no Estado do Rio Grande do Sul. Para verificar a flexibilidade dos participantes, foi utilizado o Flexiteste. Para o tratamento estatístico, foi utilizado o software IBM ® SSPS Statistics 21.0 e o programa Microsoft Excel onde foram calculadas medidas descritivas (médias, desvio padrão, frequências e porcentagens) e realizado o teste ANOVA para a comparação entre médias de amostras emparelhadas. Resultados: Através da análise de dados, foi constatado que somente três das avaliações de flexibilidade nos atletas, foram estatisticamente significantes. Somente na abdução de quadril, flexão lateral de tronco esquerda e direita se encontrou resultados significativos, o restante não teve muita alteração na comparação dos resultados. Conclusão: Com os dados coletados, podemos concluir que os lutadores de Jiu-jitsu, não adquirem completa flexibilidade articular de quadril, com o treinamento esportivo somente, sendo assim os atletas precisam procurar um treinamento específico para atingir bons níveis e melhoria de desempenho durante as lutas (sic).
Keywords: Jiu-jitsu; Amplitude de movimento articular; Articulação de quadril